Self-evaluation of Polish midwives’ health state - Iwanowicz-Palus, Grażyna J.; Bień, Agnieszka M.; Stadnicka, Grażyna; Golonka, Ewa (Polish Journal of Public Health, 2012)
Introduction. Legal provisions enacting midwives’ works take for granted their ability to evaluate newborns’ and females’ health state in all stages of their lives. Aim. The work aimed at presenting a self-evaluation of health situation that midwives made, together with determinants for this self-evaluation. Material and methods. The research involved 3569 midwives from all over Poland. The research material was collected over one year. The data were collected by means of poll diagnostic method, and the questionnaire technique was used. Results. Over a half of the researched midwives – whatever region of Poland they came from (p>0.05) – evaluated their health (57.44%) and physical condition (54.89%) as good. Only few midwives admitted their health state was bad and very bad (2.72%), and made the same evaluation of their physical condition (2.63%). The majority of midwives (63.35%) declared that their health state was comparable to that of their peers, whereas a group who thought it to be considerably worse was over tenfold smaller (6.33%). Midwives who evaluated their health state as very good mostly belonged to statistically significant, varied (p<0.001) groups of individuals comprised: the youngest, aged under 30, single, childless, with higher education completed and a short work experience, highly appreciating their housing, material conditions and their life standards. Conclusions. Midwives who were very satisfied with their health state were the youngest unmarried people, childless with higher vocational education; they enjoyed a good material status and evaluated their health higher than their peers.